Teknologi Marketplace dan E-Commerce dalam Jual Beli Menurut Fiqih Muamalah - Kartika, Rini Fatma; Mubarak, M. Abdul; Nurcahyati, Ai; Ramadhan, M. Rizki; M. Azzami, Andi; Rosfiani, Okta; Rinaldi, Riki (Journal Evidence Of Law, 2024)
The purpose of this study is to determine whether online sales through marketplaces and e-commerce are compliant with Islamic law that can be upheld. This study anticipates problems that sellers, buyers, and shipping companies may encounter in Islamic law. This type of research methodology is known as theoretical sketching, which involves conducting literature reviews on books that discuss the use of marketplace and e-commerce technology in the sale of goods in accordance with Islamic law. Additionally, research is conducted on journals and the internet regarding the subject matter and the role of Islamic law in addressing it. The conclusion drawn from this research is that marketplace and e-commerce technologies in the context of buying and selling do not conflict with Islamic law, which is the principle of mutual benefit between one person and another. By paying with a unique code, both parties will not feel cheated, hence reducing pressure and selection. Because marketplaces and e-commerce are platforms with the function of third parties, they are sometimes referred to as sales and purchase channels in the course of the buying and selling process.